Brain abnormalities, neurodegeneration, and dysosteosclerosis (BANDDOS): new cases, systematic literature review, and associations with CSF1R-ALSP - Jarosław Dulski; Josiane Souza; Mara Lúcia Santos; Zbigniew K. Wszolek (Orphanet Journal of Rare Diseases, 2023)
Abstract CSF1R mutations cause autosomal-dominant CSF1R-related leukoencephalopathy with axonal spheroids and pigmented glia (CSF1R-ALSP) and autosomal-recessive brain abnormalities, neurodegeneration, and dysosteosclerosis (BANDDOS). The former is increasingly recognized, and disease-modifying therapy was introduced; however, literature is scarce on the latter. This review analyzes BANDDOS and discusses similarities and differences with CSF1R-ALSP. We systematically retrieved and analyzed the clinical, genetic, radiological, and pathological data on the previously reported and our cases with BANDDOS. We identified 19 patients with BANDDOS (literature search according to the PRISMA 2020 guidelines: n = 16, our material: n = 3). We found 11 CSF1R mutations, including splicing (n = 3), missense (n = 3), nonsense (n = 2), and intronic (n = 2) variants and one inframe deletion. All mutations disrupted the tyrosine kinase domain or resulted in nonsense-mediated mRNA decay. The material is heterogenous, and the presented information refers to the number of patients with sufficient data on specific symptoms, results, or performed procedures. The first symptoms occurred in the perinatal period (n = 5), infancy (n = 2), childhood (n = 5), and adulthood (n = 1). Dysmorphic features were present in 7/17 cases. Neurological symptoms included speech disturbances (n = 13/15), cognitive decline (n = 12/14), spasticity/rigidity (n = 12/15), hyperactive tendon reflex (n = 11/14), pathological reflexes (n = 8/11), seizures (n = 9/16), dysphagia (n = 9/12), developmental delay (n = 7/14), infantile hypotonia (n = 3/11), and optic nerve atrophy (n = 2/7). Skeletal deformities were observed in 13/17 cases and fell within the dysosteosclerosis – Pyle disease spectrum. Brain abnormalities included white matter changes (n = 19/19), calcifications (n = 15/18), agenesis of corpus callosum (n = 12/16), ventriculomegaly (n = 13/19), Dandy-Walker complex (n = 7/19), and cortical abnormalities (n = 4/10). Three patients died in infancy, two in childhood, and one case at unspecified age. A single brain autopsy evidenced multiple brain anomalies, absence of corpus callosum, absence of microglia, severe white matter atrophy with axonal spheroids, gliosis, and numerous dystrophic calcifications. In conclusion, BANDDOS presents in the perinatal period or infancy and has a devastating course with congenital brain abnormalities, developmental delay, neurological deficits, osteopetrosis, and dysmorphic features. There is a significant overlap in the clinical, radiological, and neuropathological aspects between BANDDOS and CSF1R-ALSP. As both disorders are on the same continuum, there is a window of opportunity to apply available therapy in CSF1R-ALSP to BANDDOS.